Interest Benefits from the Debt Crisis to the German Budget: Updated Calculations - Reint E. Gropp; Oliver Holtemöller (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2015)
In a recent IWH online note, the IWH suggested that due to “flight to safety” effects, Germany was able to issue government debt at lower rates than otherwise would have been possible. The total savings was calculated to be around Euro 100 billion or about 3 percent of German GDP. This note provides further evidence on the interest savings to the German budget that extend the calculations in two dimensions. Using this refined methodology, we obtain interest savings to the German budget of just under Euro 90 billion.
urn:nbn:de:gbv:3:2-48505
Keywords: 330; European Union; Greek crisis; government bonds; German public budget; Greece; Germany